2016
DOI: 10.1016/j.ahj.2015.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Excess weight and life expectancy after acute myocardial infarction: The obesity paradox reexamined

Abstract: Background An “obesity paradox” has been described in patients with acute myocardial infarction (AMI), whereby obese and overweight patients have a lower risk of short-term mortality after AMI than normal weight patients. However, the long-term association of obesity with mortality after AMI remains unknown. Methods We used data from the Cooperative Cardiovascular Project, a prospective medical record study of Medicare beneficiaries hospitalized with AMI with 17 years of follow-up (N=124,981), to evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
1
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 31 publications
4
35
1
5
Order By: Relevance
“…However, weight loss was not associated with SCD and nonfatal MI [30]. Our study also explains the same, there is no association found between SCD, nonfatal MI and weight loss.…”
Section: Discussionsupporting
confidence: 67%
“…However, weight loss was not associated with SCD and nonfatal MI [30]. Our study also explains the same, there is no association found between SCD, nonfatal MI and weight loss.…”
Section: Discussionsupporting
confidence: 67%
“…The function of large arteries may also be an important factor. Obesity is associated with impaired function of large arteries, which might be affected by metabolic dysregulation and inflammatory pathways . A study found an association between excess body weight and increased vascular stiffness in adults as young as 20‐30 years of age, highlighting the effect of obesity since a very early stage of vascular aging .…”
Section: Introductionmentioning
confidence: 99%
“…Так, метаанализ 89 исследова-ний, включавших более 1,3 млн человек с диагнозом ИБС, показал что при избыточной массе тела и ожирении риск кардиоваскулярных событий ниже, чем у пациентов с нормальным ИМТ [14]. У лиц с ожирением отдаленный прогноз ИМ оказался более благоприятным, чем у лиц без избытка массы тела и ожирения [15,16]. Сходные результаты были полу-чены применительно к отдаленному прогнозу острых нарушений мозгового кровообращения (ОНМК) [17].…”
Section: существуетunclassified